Supernumerary muscle of tarsal tunnel: a case report - Rituparna Basu; Karabi Baral; Jayanta Sarkar; Koushik Ray; Bileswar Mistry (Wolters Kluwer Medknow Publications, 2016)
Supernumerary muscles are an infrequent finding during dissections around the ankle. This report focusses on the finding of one such muscle which was found in the tarsal tunnel of the left lower limb unilaterally during routine dissection of a 70 year old male cadaver in Bankura Sammilani Medical College, West Bengal. This supernumerary muscle had a single head of origin from the flexor hallucis longus and posterior intermuscular septum and was traced to its insertion into the flexor digitorum accessorius in the sole and hence was named flexor digitorum accessorius longus, and its relations with the neurovascular bundle were noted. Flexor digitorum accessorius longus may be a cause of tarsal tunnel syndrome so it should be kept in mind during its management. It may also produce symptoms mimicking soft tissue tumors. Thus knowledge of this muscle will be of utmost importance to anatomists, clinicians, radiologists and athletes.